Single undertaking : a straitjacket or variable geometry? - Patel, Chandrakant (South Centre GenevaCH, 2003)
Identifies and places foremost an understanding of the meaning of the term single undertaking. Provides a historical overview to the introduction of the concept of single undertaking in the Punta del Este Declaration. Traces the evolution of single undertaking from before the Uruguay Round to its conclusion. Sets forth some arguments to show that in multilateral trade negotiations, agenda setting, conduct and outcome of the processes are largely driven by trade weights, not by diplomacy.